Entangled embodiment(s) with trauma: a play in six acts - Kelley, Amber; Gale, Jerry (Murmurations: Journal of Transformative Systemic Practice, 2022)
Exposition This play is about entangled embodiments of early career family therapists attending to clients’ trauma. It is drawn from research based on the theoretical framework of Karen Barad’s agential realism. As part of (2007) agential realism, the world is always already entangled and connected (Barad, 2007). I/we are not separate from one another, as in a murmuration, a shifting mass of starlings, thousands of birds flying together in dynamic shapes, shifting and moving in concert, responsive to one another and their larger environment (RSPB, 2022). In performing a murmuration, the birds cease to be distinct but instead are connected, communicating, and entangled as part of the larger form that is ever changing and becoming, allowing us to consider how thinking of systemic practice as a murmuration entails following lines of entanglement, connectedness, and iterative responsivity. To trace and track a murmuration, to learn from it and be a part of the embodied entanglement, is not to sit still, but to follow embodied shifts, to draw temporary and moving boundaries around the amorphous shapes and patterns that are forming/dissolving/re-forming in turn. Barad, a feminist quantum physicist (2007), refers to these boundary-drawing practices as agential cuts, or enactments that show what is inside/outside a phenomenon, not as inherently distinct, but as temporarily separated so the murmuration can be looked at, examined, and explored. This play is a series of agential cuts, six acts that together provide a broader narrative. This narrative weaves through/in/between the murmuration of systemic practice, exploring with curiosity what happens to the embodiments of systemic therapy practitioners when a client discloses a traumatic event or history. Based on Amber Kelley’s dissertation research, and presenting findings as poetry, this play follows an arc of exploration, an embodied journey through the entangled becomings of therapy practice and of being intimately with/in the trauma of our interconnected world.